Building Healthy Northern Communities Through Strengthening Capacity (Journal of Comparative Social Work, 2012)
This study examines and evaluates the effects of one-time funding on capacity building of health and social welfare organizations in a remote and northern section of British Columbia Canada. The Province of British Columbia awarded a two million dollar grant (Canadian) to the University of Northern British Columbia (UNBC). Organizations applied for funds through a competitive process that was managed by the School of Social Work at UNBC. Twenty-five different community organizations and agencies received funding for a period of eighteen months. The organizations and agencies delivered a range of services and activities located in remote First Nations communities as well as the natural resource-based single industry towns of northern BC.